Effects of Different Levels of Metabolizable Energy and Formulation of Diet Based on Digestible and Total Amino Acid Requirements on Performance of Male Broiler - Ghaffari, M.; Shivazad, M.; Zaghari, M.; Taherkhani, R. (International Journal of Poultry Science, 2007)
In order to evaluate the effects of different levels of energy and method of formulation of Amino Acid (AA) requirements of diets, this experiment was conducted using 294 male broiler chicks. The experiment was carried out using a complete block design with a 7×2 factorial arrangement. Factors were included different level of energy (7 energy levels) and method of formulation of diets AA requirements (total and digestible). Method of formulation of AA requirement had no significant effect on cumulative feed consumption. Formulation of diet based on total or digestible AA had no significant effect on weight gain whereas high ME diets resulted in higher weight gain. Diets formulated based on total or digestible AA had feed conversion ratios that were not significantly different. Abdominal fat pad were significantly lower in chicks fed diets formulated on digestible AA basis. Energy content of diets affected fat pad significantly. Abdominal fat pad increased significantly as ME content of diets increased. Results obtained in our study suggest that even whit corn soybean meal based diets, formulation of diets AA requirement may be a beneficial tool for optimization of performance.